Pengembangan Bahan Ajar Matematika Untuk Meningkatkan Kemampuan Pemecahan Masalah Menggunakan Model Pembelajaran Reciprocal Teaching di Kelas VII SMP N 1 Barumun - Sundut Azhari Hasibuan; Nur Hani Hasibuan; Kholidah Sitanggang (Manna wa Salwa Foundation (Yayasan Manna wa Salwa), 2026)
So far, the use of teaching materials in class VII of SMP N 1 Barumun is still less interesting and the learning method tends to be teacher-centered. Students' problem-solving abilities are also still poor with a percentage of student completion in the pre-test of 16.67%. So in an effort to improve students' mathematical problem-solving abilities, one of them is by developing teaching materials using the reciprocal teaching model. The teaching materials developed are teacher books, student books, lesson plans and student worksheets. This study aims to determine how to develop teaching materials to improve problem-solving abilities using the reciprocal teaching model in class VII of SMP N 1 Barumun in the 2024/2025 academic year. This research is a research and development (R&D). Using the 4D development model. The results of this study indicate that: (1) The validity of the teaching materials gets a value of 90% which is in the